แบบจำลองสถานการณ์ในการดำเนินการขนส่งสินค้าแบบเต็มคัน - ฐิตินันท์ ผลสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
To develop a simulation program for analyzing full truckload operation under uncertain demand and loading/unloading times. Given a dataset provided by a truckload carrier in Thailand, the study employs the commercial package named "ExtendSim8" to simulate the operation of the case company that serves its customers from two terminals. The complete simulation model consists of 6 sub-models: (1) Demand Arrival model (2) Line-haul Operation model (3) Loading Operation model (4) Unloading Operation model (5) Truck assignment model and (6) Truck Subcontracting model. The developed simulation model can be used to assess the trucking cost under alternative truck assignment strategies while considering the implications of randomness in customer demands and loading/unloading times.